Research on language evolution in the second decade of the 21st century - Szczepańska, Aleksandra; Poniewierska, Aleksandra; Wacewicz, Sławomir; Żywiczyński, Przemysław (Język(i) w czasie i przestrzeni, 2021)
Despite the anciency of the question of how language emerged, it was only in the 1990s that language evolution began to take shape as an independent and fully-fledged field of study. This paper aims to make the reader familiar with the most recent changes and research aspects that we see as having had the most transforming influence on the science of language evolution over the past decade: an increase of interest trends in this relatively new field of research. We address three in the topics of multimodality and iconicity (with an increasing involvement of experimental studies), the use of new types of data and ways of acquiring data (in particular, enabling statistical inferences from big datasets), and – last but not least – key identity-forming institutional changes, such as the foundation of specialised conferences and journals.